Dutch commerce and Chinese merchants in Java : colonial relationships in trade and finance, 1800-1942 - Claver, Alexander (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde ;, 2014)
Dutch Commerce and Chinese Merchants in Java describes the vanished commercial world of colonial Java. Alexander Claver shows the challenges of a demanding business environment by highlighting trade and finance mechanisms, and the relationships between the participants involved.